Analisis Ketersediaan dan Kebutuhan Air Sub DAS Rupit Menggunakan Remote Sensing dan GIS: Analysis of Water Availability and Demand in the Rupit Sub-Watershed Using Remote Sensing and GIS - Nurhikmawaty; Putranto, Dinar Dwi Anugerah; Hadinata, Febrian (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2024)
The water balance of a river basin is crucial for estimating water availability to meet current and future domestic and economic water demand and supply. Parameters such as rainfall, temperature, evapotranspiration, deficit, and surplus soil water content determine the water availability of a river basin (DAS), influenced by factors like land use, soil type, seasonal variations, and other environmental factors. This research aims to estimate the water balance of the Rupit sub-watershed using the FJ Mock model. The Sentinel 1 image of the area was processed to produce a land use map. GIS modeling generated maps of rainfall, land use, soil, slope, morphometry catchment, excess moisture, evapotranspiration, and surface run-off. The analysis reveals that the highest rainfall and evapotranspiration occur in January, while other months average around 56 - 66 mm per month. Excess water during the wet months (November-March) leads to flooding, damaging infrastructure such as residential buildings, roads, and bridges. Conversely, April-October experiences water shortages. The annual weighted watershed deficit is 46.6 mm, with almost no surplus detected. Rainfall run-off simulations demonstrate significant and coherent watershed responses to rainfall patterns. Due to low rainfall and soil moisture levels from preceding months, March exhibits the highest discharge at 15.35 m3/s, with a run-off coefficient of 0.863.